2001
DOI: 10.1128/aem.67.2.982-985.2001
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia cepacia Genomovar III Is a Common Plant-Associated Bacterium

Abstract: A polyphasic taxonomic study involving DNA-DNA hybridization, whole-cell protein electrophoresis, and 16S ribosomal DNA sequence analysis revealed that a group of Burkholderia cepacia-like organisms isolated from the rhizosphere or tissues of maize, wheat, and lupine belong to B. cepacia genomovar III, a genomic species associated with "cepacia syndrome" in cystic fibrosis patients. The present study also revealed considerable protein electrophoretic heterogeneity within this species and demonstrated that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
95
1
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 137 publications
(102 citation statements)
references
References 14 publications
3
95
1
3
Order By: Relevance
“…(41). The sensitivity and specificity of some or all of the above-mentioned media for the isolation of environmental "B. cepacia" isolates may be much lower (17), and therefore the use of other media, like PCAT medium (containing azelaic acid and tryptamine) (12) or TB-T medium (containing glucose, asparagine, trypan blue, and tetracycline) (38) may be recommended (4,109).…”
Section: Identification Of B Cepacia Complex Organismsmentioning
confidence: 99%
“…(41). The sensitivity and specificity of some or all of the above-mentioned media for the isolation of environmental "B. cepacia" isolates may be much lower (17), and therefore the use of other media, like PCAT medium (containing azelaic acid and tryptamine) (12) or TB-T medium (containing glucose, asparagine, trypan blue, and tetracycline) (38) may be recommended (4,109).…”
Section: Identification Of B Cepacia Complex Organismsmentioning
confidence: 99%
“…Burkholderia cenocepacia belongs to the Burkholderia cepacia complex (Bcc), a group of ten phenotypically similar environmental Gram-negative bacteria (Balandreau et al, 2001), which are also opportunistic human pathogens causing chronic, sometimes fatal, pulmonary infections in cystic fibrosis (CF) patients (Isles et al, 1984;Mahenthiralingam et al, 2005). Treatment of these infections is difficult as Bcc bacteria are inherently resistant to most clinically relevant antimicrobial agents (Aaron et al, 2000;Burns et al, 1996;Gold et al, 1983), including antimicrobial peptides (APs) (Loutet et al, 2006;Turner et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…A number of previous studies have demonstrated transmission of B. cepacia complex strains between persons with CF (for reviews, see references 15, 16, 21, and 22). More recent studies indicate that the natural environment is also a likely reservoir for acquisition of B. cepacia complex strains (4,24). Better risk assessment of potential sources of infection and the development of optimal infection control policies rely on a more complete understanding of the molecular epidemiology of B. cepacia complex infection in CF.…”
mentioning
confidence: 99%